2007
DOI: 10.1016/j.mcn.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP4 is a novel RhoGAP that mediates inhibition of cell motility and axon outgrowth

Abstract: This report examines the structure and function of ARHGAP4, a novel RhoGAP whose structural features make it ideally suited to regulate the cytoskeletal dynamics that control cell motility and axon outgrowth. Our studies show that ARHGAP4 inhibited the migration of NIH/3T3 cells and the outgrowth of hippocampal axons. ARHGAP4 contains an N-terminal FCH domain, a central GTPase activating (GAP) domain and a C-terminal SH3 domain. Our structure/function analyses show that the FCH domain appears to be important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 33 publications
1
61
0
1
Order By: Relevance
“…4A). Overexpression of p115 RhoGAP in control cells also decreased basal migration, which is consistent with the previous report that p115 RhoGAP inhibits cell motility in NIH3T3 cells (31). In addition, p115 RhoGAP knockdown by siRNA enhanced cell migration in both control and PRL-1-expressing cells (Fig.…”
Section: Structural Basis Of Prl-1 Interaction With Peptide 1 and Thesupporting
confidence: 92%
See 1 more Smart Citation
“…4A). Overexpression of p115 RhoGAP in control cells also decreased basal migration, which is consistent with the previous report that p115 RhoGAP inhibits cell motility in NIH3T3 cells (31). In addition, p115 RhoGAP knockdown by siRNA enhanced cell migration in both control and PRL-1-expressing cells (Fig.…”
Section: Structural Basis Of Prl-1 Interaction With Peptide 1 and Thesupporting
confidence: 92%
“…It has also been reported that p115 RhoGAP inhibits cell motility through its GAP and C-terminal SH3 domains (31). To understand the functional significance of the novel interaction between PRL-1 and p115 RhoGAP, we evaluated the effect of modulating the expression of p115 RhoGAP on PRL-1-mediated cell migration as well as on ERK1/2 and RhoA activity.…”
Section: Structural Basis Of Prl-1 Interaction With Peptide 1 and Thementioning
confidence: 99%
“…Despite this apparent contradiction, there is a precedent for our finding. It has been reported that the small GTPase regulator ARHGAP4 is recruited to the leading front of 3T3 cells where it inhibits their motility (Vogt et al, 2007). Thus, β-PIX in keratinocytes and ARHGAP4 in 3T3 cells may act as brakes to cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…The RhoGAP domain of srGAP1 has been shown to promote GTP hydrolysis of Cdc42 and RhoA, depending on the concentration of Slit1 (Wong et al, 2001), whereas the GAP domains of srGAP2 and srGAP3 are both specific for Rac1 (Guerrier et al, 2009;Soderling et al, 2002), and ArhGAP4 can act on both Cdc42 and Rac1 (Vogt et al, 2007). All four family members display spatially and temporally distinct patterns of expression in the central nervous system (Bacon et al, 2009;Foletta et al, 2002) and have been shown to regulate cell migration and neuronal morphology in mammalian cells (Guerrier et al, 2009;Soderling et al, 2002;Vogt et al, 2007;Wong et al, 2001;Yang et al, 2006), a function that seems evolutionary conserved in invertebrates (Zaidel-Bar et al, 2010). srGAP3 has been implicated in a severe form of mental retardation, the 3p2 syndrome, giving srGAP3 the alternate name of mental-disorder associated GAP protein (MEGAP) (Endris et al, 2002).…”
Section: Introductionmentioning
confidence: 99%